2006
DOI: 10.2174/092986706778201684
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine and Other Preventive Measures for Contrast-Induced Nephropathy in the Intensive Care Unit

Abstract: The increase in diagnostic imaging procedures that require infusion of intravenous radiographic contrast has led to a parallel increase in the incidence of contrast-induced nephropathy (CIN). Since CIN accounts for a significant increase of hospital-acquired renal failure, length of stay and mortality, several additive strategies to prevent CIN are presently advocated, including N-acetylcysteine (NAC), sodium bicarbonate, theophylline or fenoldopam, and peri-procedural hemofiltration/hemodialysis. As only one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Experimental studies have shown systemically delivered NAC reduces the permanent hearing loss associated with noise trauma, impulsive noise trauma and ototoxicity (summarized in ). The drug is currently used clinically, having been shown to reduce the incidence and severity of contrast-induced neuropathy (Sanaei-Ardekani et al, 2005;Schultz et al, 2006). It has also been used in clinical trials aimed at reducing reperfusion injury following knee surgery (Ege et al, 2006;Saricaoglu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have shown systemically delivered NAC reduces the permanent hearing loss associated with noise trauma, impulsive noise trauma and ototoxicity (summarized in ). The drug is currently used clinically, having been shown to reduce the incidence and severity of contrast-induced neuropathy (Sanaei-Ardekani et al, 2005;Schultz et al, 2006). It has also been used in clinical trials aimed at reducing reperfusion injury following knee surgery (Ege et al, 2006;Saricaoglu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…CIN is an acute deterioration of renal function after administration of iodinated contrast media in the absence of another cause 6,7 . In clinical studies, it has been defined as an increase in 25% or more, or an absolute increase of 0.5 mg/dL (44.2 µmol/L) or more of serum creatinine from baseline 6–12 . The pathogenesis of CIN is incompletely understood but is thought to be because of a complex interaction of various mechanisms such as decreased renal blood flow as a result of vasoconstriction, direct tubular toxicity by oxidized free radicals and an osmotic effect 13 .…”
Section: Discussionmentioning
confidence: 99%
“…6,7 In clinical studies, it has been defined as an increase in 25% or more, or an absolute increase of 0.5 mg/dL (44.2 mmol/L) or more of serum creatinine from baseline. [6][7][8][9][10][11][12] The pathogenesis of CIN is incompletely understood but is thought to be because of a complex interaction of various mechanisms such as decreased renal blood flow as a result of vasoconstriction, direct tubular toxicity by oxidized free radicals and an osmotic effect. 13 CIN is a major health issue, and is the third most important cause of hospitalacquired renal failure.…”
Section: Discussionmentioning
confidence: 99%